2015
DOI: 10.3923/ajava.2015.875.884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In ovo Injection of L-Carnitine at Different Incubational Ages on Egg Hatchability in Broiler Breeders and Post-Hatch Performance

Abstract: An experiment was conducted to investigate the effect of in ovo L-carnitine injection at three incubational ages on hatchability of broiler breeders and post-hatch performance. Four doses of L-carnitine (0.0, 4, 8 and 12 mg/100 μL) were injected into fertile eggs at days 14, 16 and 18 of incubation. Hatched chicks were individually weighed and fertile hatchability was calculated. Birds were kept in batteries and fed common starter and grower diets. Means of weight gain, feed intake and feed conversion were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…It is far from completely understood [29]. These inconsistent results appearing in the literature concerning the responsiveness to in ovo injection of L-carnitine might have resulted from many factors such as differences in strains and age of breeder hens, injection technique, site of in ovo injection, timing of injection (incubational age), dose and so on [30].…”
Section: Biochemical Indices (Sgot and Sgpt)mentioning
confidence: 99%
“…It is far from completely understood [29]. These inconsistent results appearing in the literature concerning the responsiveness to in ovo injection of L-carnitine might have resulted from many factors such as differences in strains and age of breeder hens, injection technique, site of in ovo injection, timing of injection (incubational age), dose and so on [30].…”
Section: Biochemical Indices (Sgot and Sgpt)mentioning
confidence: 99%
“…It is far from completely understood [40]. These inconsistent results appearing in the literature concerning the responsiveness to in ovo injection of L-carnitine might have been resulted from many factors such as differences in strains and age of breeder hens, injection technique, site of in ovo injection, timing of injection (incubational age), dose, and so on [41].…”
Section: Biochemical Indices (Sgot and Sgpt)mentioning
confidence: 99%
“…At the same time, an increase in the absolute and specific weight of chicks at hatching, glycogen content in the liver and pectoral muscle, and the insulin-like growth factor in plasma was observed 9 . Another study found that L-carnitine injection significantly increased hatchability, increased chick growth rate, and improved feed conversion 10 , on day 14 of the incubation.…”
Section: Introductionmentioning
confidence: 97%
“…The biostimulant administration time in the non-invasive method is most often before incubation or before transfer to hatchers; in the in ovo injection method, on different days of incubation (studies are known for biostimulant administration at days 0, 7, 11, 12, 14, 16, 17, 17, 5, 18, and 21) [3][4][5][6][7][8][9][10][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%